Properties and Degradability of Hydrothermal Carbonization Products. Issue 5 (1st September 2013) - Eibisch, Nina; Helfrich, Mirjam; Don, Axel; Mikutta, Robert; Kruse, Andrea; Ellerbrock, Ruth; Flessa, Heinz
Abstract : Biomass carbonized via hydrothermal carbonization (HTC) yields a liquid and a carbon (C)‐rich solid called hydrochar. In soil, hydrochars may act as fertilizers and promote C sequestration. We assumed that the chemical composition of the raw material (woodchips, straw, grass cuttings, or digestate) determines the properties of the liquid and solid HTC products, including their degradability. Additionally, we investigated whether easily mineralizable organic components adsorbed on the hydrochar surface influence the degradability of the hydrochars and could be removed by repetitive washing. Carbon mineralization was measured as CO2 production over 30 d in aerobic incubation experiments with loamy sand. Chemical analysis revealed that most nutrients were preferably enriched in the liquid phase. The C mineralization of hydrochars from woodchips (2% of total C added), straw (3%), grass (6%), and digestate (14%) were dependent on the raw material carbonized and were significantly lower (by 60–92%; p < 0.05) than the mineralization of the corresponding raw materials. Washing of the hydrochars significantly decreased mineralization of digestate‐hydrochar (up to 40%) but had no effect on mineralization rates of the other three hydrochars. Variations in C mineralization between different hydrochars could be explained by multiple factors, including differences in the O/C–H/C ratios, C/N ratios, lignin content, amount of oxygen‐containing functional groups, and pH. In contrast to the solids, the liquid products were highly degradable, with 61 to 89% of their dissolved organic C being mineralized within 30 d. The liquids may be treated aerobically (e.g., for nutrient recovery).